Analisis Tingkat Kepercayaan Generasi Milenial di Media Sosial Pada Konten Hoaks Buatan Artificial Intelligence (Ai) - Ramadhan Hidayattulloh; Yunisca Nurmalisa; Ana Mentari; Hermi Yanzi; Karyadi Hidayat (Jurnal Pendidikan Sosial Dan Konseling, 2026)
The development of Artificial Intelligence (AI) has increased the spread of digital hoaxes that are difficult to distinguish from authentic information. This study aims to analyze millennials' level of trust in AI-generated hoax content on social media. A descriptive quantitative method was employed, with data collected through questionnaires and interviews involving social media users aged 25–40 years in Dusun 3, Sukapura Village, Sragi District, South Lampung Regency. The analysis focused on content format, exposure intensity, display credibility, information dissemination patterns, and trust in digital information. The findings reveal that millennials are relatively vulnerable to AI-based hoaxes, particularly visual and audiovisual content that appears realistic and convincing. Although some respondents demonstrated critical attitudes toward digital information, there remains a tendency to trust content that is emotional and aligned with personal beliefs. The study highlights the importance of strengthening digital literacy, critical thinking skills, and information verification practices to enhance public resilience against AI-based disinformation.